EPIDEMIOLOGY OF MALIGNANT TUMORS OF MAXILLAE, MANDIBLE AND FACIAL AREA BASING ON STATISTICAL DATA OF POLTAVA AND POLTAVA REGION - Bashtan, V.P.; Mukovoz, O.Y.; Riznyk, B.M.; Pichkur, I.M.; Tarakanova, O.I. (World of Medicine and Biology, 2012)
Due to creation of computer-assisted data system of the National cancer register, monitoring of malignant tumors of maxillae, mandible and facial area become possible as well as updating of data on each patient that is accounted for, treatment that he is being administered and the last date he was clinically examined. All that enables the rational supervision on the patients with pre-malignancies and planning of technical and staff supply of oncology service. Besides, in cases of early diagnosis, it is possible to administer complex treatment with primary modeling of operations that will be ensued by prosthesis installment for adequate patient rehabilitation.